2014
DOI: 10.1108/h-12-2012-0026
|View full text |Cite
|
Sign up to set email alerts
|

Competition for donations and the sustainability of not-for-profit organisations

Abstract: Purpose – The purpose of this paper is to understand the nature of competition for private donations that occurs between not-for-profit organisations (NPOs). This competition occurs because NPOs do not produce commercially viable outputs and therefore rely on donations. The financial sustainability of NPOs is problematic, both individually and in economy-wide terms, as they do not produce commercial saleable outputs. Instead they raise funds by either relying on government grants or competing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
2
22
0
2
Order By: Relevance
“…The biggest takeaway from this study is that capital campaigns at project‐pursuing nonprofits may improve fundraising conditions at community nonprofits. Therefore, this study offers additional support to the existing literature on fundraising effects by demonstrating that contributions to nonprofits are positively associated with fundraising performance (Twu ), and that fundraising activities at one nonprofit can affect the overall distribution of resources among neighboring nonprofits (Lyons ; Omura and Forster ). Further, this study is one of two studies that examines the effects of bricks‐and‐mortar construction projects on nonprofit financial performance (Woronkowicz ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The biggest takeaway from this study is that capital campaigns at project‐pursuing nonprofits may improve fundraising conditions at community nonprofits. Therefore, this study offers additional support to the existing literature on fundraising effects by demonstrating that contributions to nonprofits are positively associated with fundraising performance (Twu ), and that fundraising activities at one nonprofit can affect the overall distribution of resources among neighboring nonprofits (Lyons ; Omura and Forster ). Further, this study is one of two studies that examines the effects of bricks‐and‐mortar construction projects on nonprofit financial performance (Woronkowicz ).…”
Section: Discussionsupporting
confidence: 65%
“…Woronkowicz () examines the effects of nonprofit facilities projects on financial vulnerability and finds that, for organizations that build new facilities, capital financing can potentially have adverse impacts on overall financial vulnerability, though it is unclear whether these effects are long term. To date, however, no study has examined the impact of large capital campaigns on the fundraising success of other nonprofit organizations, and studies of how (and whether) the fundraising activity of one nonprofit affects the success of another nonprofit in the same market (Lyons ; Omura and Forster ; Twu ) have produced mixed results.…”
mentioning
confidence: 99%
“…Saiia et al, (2003) made public the refined association between the normal plan of unselfishness and therefore the developing thought of basic philanthropy standards. Omura and Forster (2014) valid the reasoning that company ventures, execution introduction goes concerning as a propelled power and has positive relationship with CSR and philanthropy (Barnett & Salomon, 2006) by their exploration structure founded that generosity rehearses do not head of association's edges rather elevate companies to require half in company mingling. Omura and Forster (2014) delineate that company execution of centred undertakings and effective power of CSR has positive reference to charity by underlining more and more solid relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Omura and Forster (2014) valid the reasoning that company ventures, execution introduction goes concerning as a propelled power and has positive relationship with CSR and philanthropy (Barnett & Salomon, 2006) by their exploration structure founded that generosity rehearses do not head of association's edges rather elevate companies to require half in company mingling. Omura and Forster (2014) delineate that company execution of centred undertakings and effective power of CSR has positive reference to charity by underlining more and more solid relationship. Barnett et al (2006) found that unselfishness practices should be levelled consistent with extent of social welfare of the Organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We argue that accounting has long been a tool suited to modes of governance that prioritize the accumulation of wealth and the individualization of the poor, which characterize present-day neoliberal policies that are often enacted through non-governmental organizations. This historical study therefore has implications for research on the roles of accounting within non-governmental organizations today, which operate in competitive markets not only for service delivery, where the poor are seen as individual clients, but also for fundraising, where the wealthy are aggressively cultivated as donors (Alexander, 2000;Froelich, 1999;Omura & Forster, 2014).…”
Section: Introductionmentioning
confidence: 99%